Performance evaluation of a second‐generation O‐ring‐shaped image‐guided radiotherapy system with a gimbal‐mounted linear accelerator and real‐time tracking capabilities - Kawata, Kohei; Kishigami, Yukako; Hirashima, Hideaki; Sawada, Yohei; Urago, Maika; Fujimoto, Takahiro; Fukuda, Tetsuo; Mizowaki, Takashi; Nakamura, Mitsuhiro (Journal of applied clinical medical physics, 2025)
Purpose OXRAY, a state‐of‐the‐art radiation therapy system commercialized by Hitachi High‐Tech Ltd. in 2023, integrates unique beam delivery and image‐guided radiation therapy (IGRT) technologies as the successor to Vero4DRT. This study evaluated the performance of this second‐generation O‐ring‐shaped linear accelerator. Methods The percentage depth dose (PDD) and off‐center ratio (OCR) were calculated using the RayStation 2023B treatment planning system with multileaf collimator‐shaped square fields. PDDs were evaluated up to a depth of 250 mm and OCRs at depths of 15, 100, and 200 mm, compared with measurements. Patient‐specific quality assurance (PSQA) was conducted for 28 volumetric‐modulated arc therapy plans and evaluated using gamma pass rates (GPRs) based on a 3%/2 mm criterion. The biaxial rotational dynamic radiation therapy (BROAD‐RT) performance was validated with 25 trajectories. A tracking experiment under rotational irradiation was performed to assess the tracking accuracy. Additionally, image‐guidance systems (kV X‐ray and kV cone‐beam computed tomography) were evaluated using anthropomorphic phantoms. The localization accuracy (LA) was determined by comparing the known offsets with the noted differences between the initial and corrected positions. Results Differences between the calculated and measured data were within the tolerance limits defined in European Society for Radiotherapy and Oncology Booklet 7 and American Association of Physicists in Medicine (AAPM) Medical Physics Practice Guideline 5.b. The median PSQA GPRs exceeded 95%, satisfying AAPM Task Group‐218 criteria. BROAD‐RT demonstrated submillimeter accuracy (within 0.4 mm), even for complex trajectories. The tracking accuracy remained within 1 mm even during rotational delivery. LA was within 0.5 mm for translational shifts and 0.5° for rotational adjustments. Conclusion OXRAY demonstrated clinically acceptable beam quality and high‐precision dose delivery outcomes. The tracking accuracy was maintained under rotational irradiation. Automatic image registration enabled accurate, reproducible patient positioning, supporting reliable IGRT implementation. These findings offer practical guidance and technical benchmarks for institutions adopting OXRAY.